Unfractionated heparin dosing requirements in the presence of inflammation during the first six months of life. Issue 177 (May 2019) - Heizer, J.W.; Schardt, T.Q.; Murphy, M.E.; Branchford, B.R.
Abstract: Background: Critically ill neonates with inflammation secondary to SIRS or sepsis often develop an acquired pro-thrombotic state. Unfractionated heparin (UFH) is commonly prescribed in this population, but these subjects often remain sub-therapeutic or require very high doses of UFH to achieve and sustain therapeutic anti-Xa activity. This is due, in part, to the unique pharmacokinetics/dynamics of this population but may also be influenced by the degree of inflammation. Objective: To evaluate UFH dosing requirements in neonates and infants <6 months of age with variable degrees of systemic inflammation. Clinical outcomes of bleeding and clotting will also be examined. Subjects/methods: A retrospective chart review was performed in infants <6 months of age treated with intravenous UFH for at least 24 h with intent to reach a goal anti-Xa of 0.3–0.7 U/mL at Children's Hospital Colorado between October 2008 and August 2014. Subjects were divided into two groups, based on their ability to achieve and maintain anti-Xa concentrations between 0.3 and 0.7 U/mL. The relationship between UFH dose (U/kg/h) and inflammatory status (using pediatric age-specific definitions for SIRS, sepsis, severe sepsis, or septic shock) was examined. Results: Seventy-three subjects were included in the analysis. Twenty-three subjects (mean age = 41.2 days ± standard deviation [SD] 52.3) achieved therapeutic anti-Xa concentrations while fifty subjects (mean age = 43.4 days ± SD 53) did not. The median UFH dose needed in subjects who achieved goal anti-Xa concentrations in the absence of SIRS or sepsis criteria was 24.5 U/kg/h (interquartile range [IQR] = 23.6–25.9) while the median dose of UFH in subjects who achieved goal anti-Xa level in the setting of infection, SIRS, or sepsis of any type was 36.1 U/kg/h (IQR = 34–43.5) (p < 0.0001). In subjects who maintained therapeutic anticoagulation, there was a direct relationship between UFH dose and the severity of inflammation as determined by pediatric SIRS/sepsis criteria. Conclusions: Maintenance of therapeutic UFH levels remains a challenge in infants, especially in those with concomitant inflammatory processes. Infection, SIRS, and sepsis of any type were collectively associated with a 32% increase in unfractionated heparin dose required to achieve and maintain therapeutic anti-Xa serum concentrations. Highlights: Inflammation appears to influence unfractionated heparin (UFH) dosing in infants. Infection, SIRS, and sepsis were linked to a 32% increase in UFH dosing requirement. Bleeding events were similar regardless of whether infants achieved anti-Xa levels. Clot resolution was similar regardless of whether infants achieved anti-Xa levels.